Stylistic Analysis of the Eschatological Narrative in the Qur’an - Sholahudin, Shofwan; Sopian, Asep (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to analyze the stylistic aspects of Surah Az-Zumar verses 71–74, focusing on the eschatological representation of the Qur'an through linguistic elements. This study employs a qualitative approach, utilizing library research. The primary data consists of Surah Az-Zumar verses 71–74 and classical and modern exegeses collected through documentation. Data analysis uses qualitative content analysis based on the Qalyubi stylistic framework, encompassing phonological, morphological, syntactic, and semantic levels. Phonological analysis reveals a consistent end-rhyme pattern and internal rhythm, reinforced by assonance and tempo variations, which create significant emotional and aesthetic impacts. Morphologically, the strategic use of passive forms, such as "sīqa" and "futiḥat," emphasizes eschatological events and enhances visual imagery, thereby building dramatic tension. From a syntactic perspective, formulaic repetition and stylistic ellipsis highlight the narrative contrast between the destinies of the inhabitants of Paradise and Hell, clarifying the divine message of justice and engaging readers emotionally. Semantically, the employment of musyākalah and muqābalah khilāfī enriches the narrative by subtly contrasting the two destinies through word choice. In conclusion, stylistic elements in Surah Az-Zumar verses 71–74 are not merely aesthetic embellishments but serve as profound theological tools, shaping readers' cognitive, affective, and spiritual experiences of eschatological reality.